Clinical and histopathological findings of a rare sinonasal glomangiopericytoma - Zahraa Noureddine El Moussaoui; Zahraa Al Najjar; Nada Diab; Zahraa Saker; Hassane Choukr; Ahmad K Aoude; Marwan Saliba; Bilal Shoumar; Mohamad Reda Noureddine El Moussaoui (University of São Paulo, 2023)
Glomangiopericytoma is a rare vascular neoplasm of the nasal cavity and paranasal sinuses that occurs during the sixth or seventh decade of life. It is categorized as a borderline tumor with low malignant potential and classified as a distinct entity of sinonasal tumors with perivascular myoid phenotype by the World Health Organization (WHO). We report the case of a 50-year-old woman with nasal obstruction and severe epistaxis. The nasal sinuses computed tomography (CT), and magnetic resonance imaging (MRI) demonstrated a 3.1 cm soft tissue mass occupying the upper part of the left nasal cavity invading the left paranasal sinuses and nasal septum, and the left eye medial rectus muscle. A total mass resection was performed by nasal endoscopy. The histological and immunohistochemical examination yielded the diagnosis of glomangiopericytoma. This case report aims to contribute to the knowledge of nasal neoplasms. The need for more data on this entity is the main obstacle to developing standardized treatment guidelines.